Relación entre tecnoestrés y burnout en el ámbito laboral - Natteri Alvarado, Francesca (2024)
Due to the increasing use of technology in the workplace, particularly exacerbated by the rise of telecommuting during the COVID-19 pandemic, a noticeable increase in technostress among workers has been observed. The purpose of this research is to identify the relationship between technostress and burnout in the workplace. The methodology employed includes an applied literature review following PRISMA criteria, and the selection of quantitative studies addressing the variables of interest in the last 10 years. Various academic databases such as Scopus, Apa PsyNet, Dialnet, Proquest, and Scielo were consulted. The obtained results indicate a positive relationship between technostress and burnout, suggesting that a higher presence of technostressors in the work environment increases the risk of workers experiencing burnout symptoms. It is essential to implement programs to assess technostress and intervene to prevent employees from suffering burnout.